Effects of the Humorous Characteristics of the School Principals on School Health - İnceler, Mehtap and Güneyli, Ahmet (Frontiers in Psychology, 2021)
In this study, teachers’ views are evaluated to determine whether there is a relationship between the humor styles of school principals and the health of an organization. The study is based on a mixed research approach with both quantitative and qualitative aspects. In the quantitative study, the teachers were asked to describe their principals’ senses of humor using the “humor behavior scale” and to evaluate the organization in which they worked using the “organizational health inventory.” In the qualitative dimension, the principals working in primary schools were interviewed and asked to evaluate their own sense of humor and school’s health. When the quantitative findings were examined, the regression results showed that a cynical humor style of school principals negatively predicts organizational health, and productive social and affirmative humor styles positively predict organizational health. In the qualitative study, the content analysis results revealed that a school administrator who uses humor effectively is capable of effectively solving problems in the school. However, it has been stated that the humor style of the school principal can have negative effects as well as positive effects. School principals are advised to recognize the teachers with whom they work and to distinguish which teachers are receptive to humor.